The 2020 update on anaphylaxis in paediatric population - Tarczoń, Izabela; Cichocka-Jarosz, Ewa; Knapp, Anna; Kwinta, Przemko (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2022)
The objective of the review is to present recent updates on anaphylaxis in paediatric population worldwide. The article summarizes the results of epidemiological studies, diagnostic methods and treatments. We present a new WAO definition of anaphylaxis (2019), which broader criteria excluding dermal symptoms should facilitate faster life-saving adrenaline use. Adrenaline remains the best treatment to manage severe symptoms and to prevent biphasic reactions. There is ongoing effort to increase adrenaline use, such as modified autoinjectors, individual training, and diversified dosing. There are five independent risk factors of lethal anaphylaxis in children, including history of asthma, almost immediate onset of symptoms, unwell appearance, tachycardia and hypotension. We also report improvements in diagnostics, like component-resolved diagnostics, and novel therapies stimulating immunotolerance. We signal the development of ICD-11 with updated coding of anaphylaxis, which corresponds better to clinical observations.